Glucagon-like peptide-1 receptor agonists in peri-operative care: Dispelling myths and unveiling insights with essential considerations for anaesthesiologists - Paggers, Larissa; Mesotten, Dieter; Stragier, Hendrik (European journal of anaesthesiology, 2025)
With the growing use of glucagon-like-peptide-1 (GLP-1) receptor (GLP-1R) agonists as anti-obesity medication it is becoming increasingly important to examine its consequences in the peri-operative period. GLP-1R agonists are known for their effects of glucose-lowering and gastroparesis the latter causing some safety concerns regarding induction of anaesthesia, more specifically the risk of pulmonary aspiration. This article gathers the available evidence on this subject in addition to the already established guidelines. Current evidence makes us assume there is indeed an increased level of gastroparesis, but there are no studies to date with evidential confirmation of a presumed elevated risk of pulmonary aspiration. Future perspectives should focus on the actual risk of pulmonary aspiration and the possible implementation of ultrasound in the preoperative assessment.